Research on the Compilation of Mechanical Design Guided Textbooks Based on Chinese University MOOCs - Zhao Xiuting; Liang Ruotian; Wang Ziyue (SHS Web of Conferences)
With the development of information technology, MOOCs (Massive Open Online Courses) have become a hot topic in the field of education. At present, there is a lack of teaching materials for mechanical design courses that are compatible with MOOCs education platforms, and there are no guiding materials for students to learn after class. Therefore, this paper takes the MOOCs of Chinese universities as a platform to discuss how to use the MOOCs platform to construct a teaching material for mechanical design. By analyzing the existing problems of mechanical design teaching and the characteristics of the MOOCs platform, a compilation scheme of mechanical design tutorial textbook suitable for the MOOCs platform was proposed, and its implementation and evaluation were carried out. The compilation and research of this textbook is conducive to promoting the use of MOOCs platform.